The cruel victory : the French Resistance, D-Day and the battle for the Vercors 1944 - Ashdown, Paddy, 1941- (William Collins, 2014)
From the bestselling and prize-winning author of 'A Brilliant Little Operation' comes the long neglected D-Day story of the largest action by the French Resistance during WWII, published to coincide with the 70th anniversary of the Normandy landings.